1980
DOI: 10.1073/pnas.77.2.847
|View full text |Cite
|
Sign up to set email alerts
|

Two species of full-length cDNA are synthesized in high yield by melittin-treated avian retrovirus particles.

Abstract: A method of activating endogenous cDNA synthesis in avian retroviruses that results in the formation of two species of full-length cDNA in high yield is described. Tests of biological activity show infectivity of at least the same order of magnitude as for full-length cDNA made by other procedures.Melittin, the major component of bee venom, is used as an alternative to nonionic detergents to make the viral envelope permeable and thus activate the endogenous RNA-dependent DNA polymerase. This compound is a toxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

1981
1981
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 41 publications
3
21
0
Order By: Relevance
“…The structural orientation of M in the intact virion is such that this protein interacts with both the glycoprotein G and the RNP protein N; evidence for this statement is based on the initial observations of VSV protein cross-linking with formalin (Brown et al, 1974) and later studies that demonstrated the formation of G :M and M :N dimers and in the presence of cross-linking agents (Dubovi & Wagner, 1977;Mudd & Swanson, 1978). Phosphorylation of M may provide a mechanism for the disruption of these interactions during uncoating.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The structural orientation of M in the intact virion is such that this protein interacts with both the glycoprotein G and the RNP protein N; evidence for this statement is based on the initial observations of VSV protein cross-linking with formalin (Brown et al, 1974) and later studies that demonstrated the formation of G :M and M :N dimers and in the presence of cross-linking agents (Dubovi & Wagner, 1977;Mudd & Swanson, 1978). Phosphorylation of M may provide a mechanism for the disruption of these interactions during uncoating.…”
Section: Discussionmentioning
confidence: 99%
“…When used in an in vitro transcription reaction mixture, melittin, the 26 amino acid polypeptide active component of bee venom, has been reported to activate the synthesis of VSV mRNA and leader RNA (Boone & Skalka, 1980). Melittin interacts with biological membranes to produce localized perturbations in the bilayer structure at sites of insertion (Williams & Bell, 1972) and, therefore, does not solubilize membranes as do non-ionic detergents.…”
Section: Activation Of the In Vitro Vs V Kinase And Transcription Reamentioning
confidence: 99%
“…ERT assays. Endogenous RT (ERT) reactions were performed as previously described (7,8), with modifications as described below. Equivalent amounts of virus particles (normalized by RT content) were incubated with melittin (100 g/ml, final concentration) at 41°C for 10 min prior to addition of ERT buffer (0.1 M Tris-HCl [pH 8.3], 25 mM NaCl, 3 mM magnesium acetate, 30 mM dithiothreitol, 1 mM dCTP, 1 mM dATP, 1 mM dGTP [final concentrations]).…”
Section: Methodsmentioning
confidence: 99%
“…We also tested melittin, an amphipathic polypeptide derived from bee venom which forms membrane pores with an average size of 3 nm and can accommodate the release of 50.7-kDa size markers from permeabilized vesicles (34). Melittin has been reported to allow synthesis of more full-length cDNA in the endogenous RT reaction compared to nonionic detergents (4,6,14,66).…”
Section: Detergent Stability Of Virionsmentioning
confidence: 99%